SOCIO-ECONOMIC FACTORS CAUSE OF OPERATING PROFIT ANIMAL FALLING RATE OF AFRICAN CATFISH (Clarias Gariepinus) TARPS SWIMMING IN CANGKRING VILLAGE, SUB- DISTRICT OF JENGGAWAH, DISTRICT OF JEMBER - Nurul Fathiyah Fauzi; Syamsul Hadi (UPT Penerbitan Universitas Jember, 2017)
The purpose of this study is included: Analyzing the socioeconomic factors that caused thedecrease in livestock farming profits tarp African catfish ponds in the study area; Knowingthe profit rate of African catfish farming pond tarp in the study area, and analyze the level ofefficiency of African catfish pond fish farming sheeting in the area of research both allocativeefficiency technical and economical. Furthermore, to achieve the three objectives referred to,then usedquantitative descriptive method with survey techniques The population in thisstudy were African catfish pond fish farmers in the village tarp Cangkring Jember District ofJenggawah efforts that have experienced a declining rate of profit. The data analysistechnique used is the analysis of Cobb - Douglass function of profit , and the frontierproduction function analysis of profit. The results of this study concluded : 1) socio-economicfactors are thought to influence the profit decline in fish farming catfish pond tarp at the sitesrun significantly at 5 % significance level α with the level of determination of 0,618; 2 ) Theaverage rates of profit breeders catfish in the study site is IDR 1.255.000,85 per businessscale or as much as IDR 484.556,31 per 1,000 fry the profitability of 42.38 %, and 3) averageuse of all inputs in the production of African catfish farming has a pool tarp technicalefficiency of 2,11, at 6,36 allocative efficiency and economic efficiency level of 13,43.